The cultural values of the Situbondo Community in an Islamic Psychology Perspective - Saifullah, Saifullah (Kependidikan Islam Fakultas Agama Islam, 2022)
This discussion aims to identify the local values of the Situbondo people. Using the phenomenological method to identify how participants perceive local values. In-depth interviews were used to collect data from three participants who were recruited using the sampling and snowball facilities. This discussion shows that the values of the Situbondo people can be divided into four levels, namely the values of man and God, man and nature, interpersonal and intrapersonal relationships. In the context of human relations with God, the concept of certain basic values of the Situbondo people recognizes the principle of volunteerism which means sincerity and gratitude. Meanwhile, the relationship between humans and nature, the ability to adapt creates ecosystems that are good for the environment.